Jerusalén compartida - Menuhin, Yehudi (Revista de Estudios Árabes, 2014)
The renowned violinist observes that since the creation of the Israeli state, Jews have become like any other nation in the world, with virtues and imperfections. Therefore, Israel and Palestine, both as new nations, should realize that pragmatism will be needed to resolve the Jerusalem question, and that sharing the Holy City is the only way to attain peace.